2021
DOI: 10.1016/j.heliyon.2021.e06140
|View full text |Cite
|
Sign up to set email alerts
|

Personal and technological skills to coach people with noncommunicable diseases: development and validation of a scale for nursing students

Abstract: Background: Current international policies converge to the need of empowering patients and families in becoming more autonomous in the self-caring and management of their noncommunicable diseases (NCDs). Given their professional scope, nurses are the most well-positioned health professionals to answer this societal challenge. In the literature, health coaching and the use of information and communication technologies (ICTs) emerge as two still under-used contributions to nursing practice in this regard. Given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Studies have shown that the personal comprehensive ability of nurses is directly related to improving nursing quality ( 19 , 20 ). Therefore, strengthening the social and personal skills of nursing students has become a priority ( 21 , 22 ). Currently, standardized training is still limited to the cultivation of theoretical knowledge and practical skills, and there is a lack of soft skills training for nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the personal comprehensive ability of nurses is directly related to improving nursing quality ( 19 , 20 ). Therefore, strengthening the social and personal skills of nursing students has become a priority ( 21 , 22 ). Currently, standardized training is still limited to the cultivation of theoretical knowledge and practical skills, and there is a lack of soft skills training for nursing students.…”
Section: Discussionmentioning
confidence: 99%